The absent hand : reimagining our American landscape - Lessard, Suzannah (Counterpoint, 2019)
"Following her bestselling The Architect of Desire, Suzannah Lessard returns with a remarkable book, a work of relentless curiosity and a graceful mixture of observation and philosophy. This intriguing hybrid will remind some of W. G. Sebald and others of Rebecca Solnit, but it is Lessard's singular talent to combine this profound book-length mosaic 'a blend of historical travelogue, architectural tour, philosophical meditation, and prose poem' into a work of unique genius, as she describes and reimagines our landscapes. In this exploration of our surroundings, The Absent Hand contends that to reimagine landscape is a form of cultural reinvention. The Absent Hand begins by observing the residual places from our country's first European settlements, and continues to the life of our cities and their eventual overflow into suburbs and wildernesses. Yet Lessard is always joining us to discuss the effects of "enclosure," of how we manage to live on and in the land, how we surround ourselves on the land with stories, roads, buildings, and ideas. Whether it's climate change altering the meaning of nature, or digital communications altering the nature of work, the global enclosure is panoramic, infiltrative, inescapable. No one will finish this book, this journey, without having their ideas of living and settling in their surroundings profoundly enriched"--